MODEL PENDAMPINGAN KELUARGA BALITA SEBAGAI UPAYA PENDIDIKAN PENCEGAHAN STUNTING DI KABUPATEN KUANTAN SINGINGI, INDONESIA - Yuka Martlisda Anwika; Oong Komar; Ace Suryadi; Elih Sudiapermana (Postgraduate, University of Mataram, 2024)
This research aims to find out what the toddlers family assistance model is as an effort to stunting prevention education in Kuantan Singingi Regency. The method used is descriptive qualitative. The results showed that family assistance starts with careful planning and coordination with various related parties, implementing and preparing target data for toddlers, collecting data on families of toddlers at risk of stunting, sorting data on babies at risk of stunting until the evaluation carries out recording and reporting to the top level. Family assistance model starts from the Stunting Reduction Acceleration Team (TPPS) at the central level, namely the BKKBN, down to the provincial level, namely representatives of the provincial BKKBN, then at the Regency/City level, namely the Regional Apparatus Organization (OPD) in the field of Regency or City Population Control, at the sub-district level, namely the Family Planning Counseling Center ( KB), village or sub-district level and the Family Assistance Team (TPK) as field agents directly provide assistance to toddlers and toddlers at risk of stunting, in addition to facilitating referrals and social assistance. Based on data, the stunting rate is decreasing from 2019-2023 in Kuantan Singingi Regency.